The Evaluation of Early Marriage Law Renewal in Indonesia - Andi Hidayat Anugrah Ilahi (Unnes Law Journal, 2021)
The study objective is to evaluate early marriage law reform implementation compared to the five regions with the highest Indonesian cases. This research is descriptive using a literature study. The data source consists of primary data consisting of laws. 16 of 2019 and the Decree Number 22 / PUU-XV / 2017 of the Constitutional Court and secondary legal sources from books, websites, journals, theses, and other sources of information that researchers can use can be justified. The data analysis method uses content analysis from its implementation in the form of regional regulations, programs, and other local government activities in implementing legal products regarding early marriage, which have a significant impact on Indonesian people" s structure of life, such as poverty, reduced educational opportunities, reproductive health hazards, risks. The findings from the research reveal that there have been many efforts by local governments in supporting legal reform which are manifested in institutional programs, working groups and community activities as efforts to mitigate and eliminate early marriage in Indonesia. However, these efforts have not been fully successful; it is necessary to enforce the article on the sanctions on the marriage law to strengthen the law.